Khyber Pakhtoonistan is a Factor in Pak-Afghan Relations: Challenges and Way Forward - Jan, Amir; Hassan, Muhammad; Abbasi, Ishrat Afshan (Progressive Research Journal of Arts & Humanities (PRJAH), 2020)
This paper aims to explore out the challenges of Pak-Afghan relations and their impact on regional peace. Despite geographical proximity and common socio-cultural legacy, Pakistan and Afghanistan failed to settle their mutual differences amicable as a result, their bilateral relations have been exploited by the regional and international power. In addition to this, KPK and Balochistan provinces of Pakistan which are the main causes of geo-political differences between Pakistan and Afghanistan have been the home of terrorism, extremism and Afghan refugees since 1980s. The paper is qualitative in nature, and based on investigation of the various events and facts in order to address the question why did Pakistan and Afghanistan failto set a mechanism to end up their mutual geo-political difference? The paper also intends to forward policy recommendations for the durable and permanent friendly relations of Pakistan and Afghanistan and their possible impacts on the region.